Crop diversification with high-value perennial seed crops drives profitability in crop rotations in northwestern Canada - Bhattarai, Keshav; Khanal, Nityananda; Thilakarathna, Malinda S.; Lupwayi, Newton Z.; Rahman, Noabur; Otani, Jennifer; Shrestha, Bharat; Lemke, Reynald L.; Kroebel, Roland (Frontiers in Agronomy, 2026)
Cropping system diversification is considered a rational management practice for improving resource-use efficiency, enhancing productivity, and optimizing farm returns in the face of climate change. However, few studies have concurrently explored the productivity, profitability, and nitrogen use efficiency (NUE) of cropping systems diversified with perennial forage seed crops. This study, conducted on dark gray Luvisolic soil in the Peace River region of northwestern Canada from 2013 to 2024, sought to address this gap. A field experiment, arranged in a split-plot design, comprised eight cropping sequences as main plots and three nitrogen (N) levels (0, 45, and 90 kg N ha-1) as sub-plots. The cropping sequences included two perennial legumes (red clover and alsike clover), three perennial grasses (creeping red fescue, meadow bromegrass, and timothy), and four annual field crops (wheat, canola, pea, and barley). Productivity was evaluated based on seed yield and expressed as canola equivalent yield (CEY), while gross revenue and gross margin were used as profitability metrics. Based on CEY and aboveground biomass yield, NUE was also assessed for uniform comparison among cropping sequences. Intermittent inclusion of red clover (a perennial legume) and meadow bromegrass (a perennial vernalizing grass) in the cropping sequence increased CEY, gross revenue, gross margin, and agronomic NUE by 95-108%, 118-174%, 191-255%, and 21–77%, respectively, compared with alternating annual wheat-canola sequences across three N fertility levels. The higher seed price of red clover and greater seed yield and price of meadow bromegrass during their production phases provided opportunities to capitalize on local market demands. The N fertilization at 45 kg N ha-1 improved the yield and profitability across all cropping sequences, whereas the 90 kg N ha-1 rate did not result in significant economic benefits in comparison. Our results provide evidence that forage seed crop-based cropping systems have the potential to reduce reliance on external N inputs and enhance the economic efficiency of production systems.